Konstruksi Pembelajaran Sejarah Islam Berbasis Teks Kajen dan Serat Cebolek dengan Pendekatan Ways of Knowing - Manggara Bagus Satriya Wijaya; Hermanu Joebagio; Sariyatun Sariyatun (JUSPI (Jurnal Sejarah Peradaban Islam), 2018)
Learning History in the Curriculum as a whole emphasizes the importance of collective memory so that inhibits the growth of critical reasoning in the Student. This review covers an alternative approach in teaching history subjects applied in senior high school. The use of the concept of critical questions and emancipatory models of "ways of knowing" by Juergen Habermas is a strategy taken by teachers in teaching history lessons that can arouse the critical awareness of student. In-depth research is done by qualitative method to know the activity of teachers and learners thoroughly at the time of learning about the history of Shaykh Ahmad Mutamakkin and the settlement of his case stipulated in the Kajen manuscript and Cebolek manuscript as enrichment of the material history Mataram Islamic Kingdom. The results showed that during the learning prose took place the teacher has succeeded in creating the creation of the process of emancipation in the students themselves. Such emancipation enables an increase in the interest of learners to create their own knowledge on the material discussed in a historical perspectiveKata kunci: local wisdom in history, critical pedagogy in teaching history, emancpatory reserach